Predictive value of postoperative prealbumin levels for detecting early-stage complications following off-pump coronary artery bypass grafting - Yanting Jia; Jun Zhang; Lei Chen; Yanhui Zhu (Frontiers in Cardiovascular Medicine)
BackgroundA pathological decrease in the serum prealbumin level is closely associated with the severity of various diseases and complications after surgery. Many patients suffer from a systemic inflammatory response and local myocardial ischemia after off-pump coronary artery bypass grafting, which is related to an adverse prognosis. This study aimed to explore the relationship between the serum prealbumin level and early complications following off-pump coronary artery bypass grafting, in addition to its predictive value.MethodsData were retrospectively collected on patients undergoing off-pump coronary artery bypass grafting from January 2014 to July 2019. The serum prealbumin level was assessed within 6–12 h after the operation. Patients were classified into two groups: the “normal” level group (≥17 mg/dl) and the “low” level group (<17 mg/dl). Univariate and multivariable analyses were performed to evaluate the predictive value of a low serum prealbumin level.ResultsOf the 1,002 patients, 553 (55.2%) had a low serum prealbumin level. The rate of pulmonary infection in the low group was significantly higher than in the normal group. Univariate analysis and multivariable analysis indicated that a low serum prealbumin level was associated with the increased incidence of postoperative pulmonary infection, pleural effusion, and new-onset atrial fibrillation.ConclusionThe serum prealbumin level following off-pump coronary artery bypass grafting serves as a crucial predictor for early major postoperative complications, such as pulmonary complications and new-onset atrial fibrillation. Early identification of high-risk patients by assessing serum prealbumin levels, in addition to the timely adjustment of treatment and care strategies, can improve patient prognosis, shorten hospital stays, and reduce healthcare expenses.